Responsibility and Direction of International Law in Regulating Transnational Dissemination of Pornography - Chen, Yuxuan (Transactions on Social Science, Education and Humanities Research, 2024)
In today’s digital age, the transnational dissemination of pornography has become increasingly accessible and prevalent, leading to serious social issues and legal challenges all around the world. The high internationalization and digitalization of the pornography crime chain are blurring the legal and regulatory boundaries between different countries. To curb the rampant proliferation of pornographic materials across borders, international law should undertake the responsibility of and assume a pivotal role in regulating and restraining the transnational dissemination of pornography to protect human rights and uphold social order. There is an urgent need for establishing international legal mechanisms to combat transnational obscenity crimes. The direction for the application of international law also lies in the enhanced cooperation among nations, the development of robust legal frameworks, and the utilization of technological innovations to counter illicit pornography networks. Furthermore, a balanced approach that respects the principles of freedom of expression while prioritizing the protection of ethical standards and societal values should be emphasized. Ultimately, by elucidating the responsibility and direction of international law in regulating the transnational dissemination of pornography, this paper aims to contribute to the global discourse on protecting human dignity and maintaining societal well-being.